The Effects of Spiritual Leadership, Incentives, and Knowledge Sharing Behavior on Employee Performance at PT Malindo Karya Lestari Pekanbaru - Richard Andelman; Layla Hafni (Institut Bisnis dan Teknologi Pelita Indonesia, 2020)
This study aims to determine the spiritual leadership, incentives and knowledge sharing behavior on employee performance at PT Malindo Karya Lestari Pekanbaru. This analysis is based on 62 respondents who are all employees of PT Malindo Karya Lestari Pekanbaru. Analysis of the data used through validity test, reliability, classic assumption test and hypothesis test, It is expected that the results of this study can be an input for the company to pay more attention in making the vision statement process, directing the employees to work better and making adjustment to the incentives provided, company management also have to report the salary of employees in accordance with the salary received by the employee to the social security every month and the company management must also pay more attention to the capacity of existing knowledge in each employee so that employee can continue to learn and sharing knowledge with other colleagues.